Model for Developing Children's Religious Character through Integration of Reciting the Koran and Commemorating Islamic Holidays - Rindu Sehati (Jurnal Pendidikan Islam, 2025)
This study aims to develop a model for fostering children’s religious character by integrating routine Qur’an recitation with the commemoration of Islamic holidays (PHBI) within a community service context through the Real Work College (KKN) program. Employing a descriptive qualitative approach, data were collected over one month through observation, interviews, and documentation involving children, parents, and local religious leaders. The findings reveal notable improvements in children’s abilities to read and memorize short surahs, perform daily prayers, maintain worship discipline, and internalize the moral virtues of Prophet Muhammad (peace be upon him). The Maulid Nabi celebration, supported by parents and community leaders, strengthened communal bonds and provided positive role models, confirming that children’s spiritual growth is significantly shaped by sociocultural environments. Challenges such as limited educational resources, varied skill levels, and time constraints highlight the need for creative learning materials, broader stakeholder involvement, and the use of digital tools in future programs. Overall, the integration of Qur’an recitation and Islamic holiday celebrations proves to be an effective strategy for instilling enduring religious values while enhancing children’s moral character and social skills.